Islamic Responses to Modernity - Helena Kaler (International Institute of Islamic Thought, 2006)
By examining the ideas of modernity and their manifestations in the ideas of Ayman al-Zawahiri and Farid Esack, this essay argues that both thinkers are deeply affected by the West’s Enlightenment ideas and differ mostly in their applications. The first part examines the idea of modernity itself, tracing its forms in the thought of Marx, Nietzsche, Weber, Schmitt, Adorno, and Horkheimer, among others. The second part traces the relationship of al-Zawahiri and Esack to the ideas of modernity, defined here as subjectivity, political agency, social fragmentation, and the rise of the nation-state. In contrast to the assertion made by some that Islamist thinkers were only affected by technological, rather than ideological, modernity, it seems that both al-Zawahiri and Esack are, ideologically, children of their time.